In vitro study of antifungal activity from selected crude weed extracts for control of sheath blight disease of rice / Nurul Ashma Mohamed - Mohamed, Nurul Ashma (Faculty of Plantation and Agrotechnology, 2018)
Sheath blight disease, caused fungi of Rhizoctonia solani is an important and serious disease that attack on rice tree ( Oryza sativa ) in worldwide. The objective of the study were to determine alternative practice of sheath blight disease using crude weed extract against fungus R.solani in vitro study. This study is the alternative way in reducing hazardous chemical, utilization as it is eco-friendly management to control sheath blight disease. Infected paddy tree with sheath blight sample collected at area Merlimau Melaka and brought to laboratory isolation of a pathogen on PDA. At selected weed extract food poison technique was used to determine antifungal activity. A total ten weed species were screening for antifungal activity against R.solani were Macaranga gigantea, Momordica charantia, Passiflora foetida, Ageratum conyzoides, Elephantopus tomentosus, Nephrolepis biserrata, Chromolena odorata, Lantana camara, Solanum torvum and Asystasia gangetica are used in this study. Among all weed extracts, only Solanum torvum has higher potential to control sheath blight disease on rice. The fungal pathogen were subjected to undergo koch postulate to determine the pathogenicity of the pathogen.